Getting Real About Suicide Prevention in the Classroom and Beyond: Using a Classroom Simulation to Create Communications for At-Risk Individuals. (August 2016) - Bal, Anjali S.; Weidner, Kelly; Leeds, Christopher; Raaka, Brian
Marketing faculties, as well as business schools in general, are placing increasing importance on finding ways to better tie theoretical concepts to real-world situations. In the article that follows, we describe a project wherein students were given an opportunity to apply core consumer behavior concepts to a simulated advertising project with the aim to prevent suicide. A post hoc qualitative survey was conducted, and a series of propositions were generated. We propose that students have high levels of recall when studying in a real-world simulation. Additionally, our findings suggested that when students use core concepts in real-world simulation projects, they are able to later apply those concepts in actual real-world situations. Finally, we propose that simulations are an effective way of teaching sensitive subject matter.